Analysis cluster of palm processing industry in Indonesia - Erfit Erfit; Yulmardi Yulmardi (Jurnal Perspektif Pembiayaan dan Pembangunan Daerah, 2018)
The purposes of this research are: 1) to analyze profile of palm processing cluster from upstream up to downstream in various regions in Indonesia; 2) to analyze strength, weakness, threats, and opportunity in palm processing industry, moreover to identify the role of existing various institutions in palm processing industry cluster in steering palm processing industry development; 3) to formulate the policy of palm processing cluster to encourage agricultural development. Data used in this research is secondary data that obtained from related institutions. Data is analyzed descriptively and quantitatively, utilizing frequency of distribution’s table, crosstable, and SWOT analysis. The result of this research concludes that Indonesia has big potential to palm processing industry, particularly in upstream industry. This thing can be seen from wide of area and palm production, which are owned. From the region side, majority wide of the area and palm production in Sumatera, from wide of area’s viewpoint is approximately 63.26% in Sumatera region, from production’s viewpoint is approximately 68.71%. In the meantime, from the downstream product, palm-processing industry in Indonesia is still limited. Less or more 100 products derived from palm in Indonesia, are only able producing 23 kinds of derived products, meanwhile in Malaysia almost reaching out 70 varieties.